2014
DOI: 10.1016/s2213-2600(14)70096-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the association of early life antibiotic prescription with asthma exacerbations, impaired antiviral immunity, and genetic variants in 17q21: a population-based birth cohort study

Abstract: Moulton Charitable Foundation and Medical Research Council.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 30 publications
3
77
0
1
Order By: Relevance
“…Consistent with our findings among children living in urban areas, birth cohort studies in Europe and the United States have shown that antibiotic use in early life is associated with asthma or current wheeze, even after adjustment for respiratory infections in early life 15, 2428 . Unlike our study, however, most of those prior studies did not account for paracetamol use, which has been linked to asthma and allergic rhino-conjunctivitis in young children 29, 30 .…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with our findings among children living in urban areas, birth cohort studies in Europe and the United States have shown that antibiotic use in early life is associated with asthma or current wheeze, even after adjustment for respiratory infections in early life 15, 2428 . Unlike our study, however, most of those prior studies did not account for paracetamol use, which has been linked to asthma and allergic rhino-conjunctivitis in young children 29, 30 .…”
Section: Discussionsupporting
confidence: 91%
“…Studies with antibiotic-treated and germ-free mice have demonstrated that lack of innate immune stimulation by commensal bacteria predisposes mice to allergic diseases such as asthma, owing to a general Th2 skewing of the immune system (Huffnagle, 2010; Marsland and Salami, 2015), and also results in more severe disease in chemically-induced models of colitis due to compromised intestinal epithelial barrier integrity (Rakoff-Nahoum et al, 2004). In humans, epidemiological data have indicated that early-life treatment with broad spectrum antibiotics is associated with an increased risk of developing allergic diseases such as asthma (Murk et al, 2011; 2011; Semic-Jusufagic et al, 2014) and may also contribute to the development of inflammatory bowel disease (Ungaro et al, 2014). Little is presently known about the immunological effects of disrupting the healthy intestinal fungal community and whether this could have beneficial or detrimental effects on inflammatory disease development.…”
Section: Introductionmentioning
confidence: 99%
“…Однако, в последние годы в некоторых исследова-ниях была установлена связь антибактериальной тера-пии в первые месяцы жизни с риском развития у детей в последующем таких заболеваний, как обструктивный бронхит и бронхиальная астма, аллергический ринит, атопический дерматит, ожирение [7][8][9].…”
Section: Background: It Is Assumed That the Severity Of The Multiple unclassified